The Gray Ghost : A Seckatary Hawkins Mystery - Schulkers, Robert F. (Robert Franc), 1890-1972 (Book collections on Project MUSE., 2016)
Seckatary Hawkins and the other boys of the Fair and Square Club try to solve mysteries while the masked marauder known as the Gray Ghost runs the riverbanks and causes mischief.